1992
DOI: 10.1128/aem.58.10.3225-3232.1992
|View full text |Cite
|
Sign up to set email alerts
|

Fungal biodegradation of lignopolystyrene graft copolymers

Abstract: White rot basidiomycetes were able to biodegrade styrene (1-phenylethene) graft copolymers of lignin containing different proportions of lignin and polystyrene [poly(l-phenylethylene)]. The biodegradation tests were run on lignin-styrene copolymerization products which contained 10.3, 32.2, and 50.4% (wt/wt) lignin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 34 publications
(26 reference statements)
1
21
0
1
Order By: Relevance
“…However, because the initial attack generally begins with a surface colonization, scanning electronic microscopy (SEM) allows direct observation of this kind of degradation 24, 25. The microorganisms' adhesion to the polymeric surface is a fundamental step in order for biodegradation to take place 26, 27…”
Section: Resultsmentioning
confidence: 99%
“…However, because the initial attack generally begins with a surface colonization, scanning electronic microscopy (SEM) allows direct observation of this kind of degradation 24, 25. The microorganisms' adhesion to the polymeric surface is a fundamental step in order for biodegradation to take place 26, 27…”
Section: Resultsmentioning
confidence: 99%
“…Only about 4% of pure polystyrene was degraded by the fungus in a parallel experiment. Production of lignin peroxidases and Mn(I1) peroxidases was observed during these experiments (Milstein et al, 1992). Polyethylene containing 6% starch was incubated with P. chrysosporium in another study (Lee et al, 1991).…”
Section: Modified Polymersmentioning
confidence: 81%
“…Although polystyrene [poly(l-phenylethylene)] is highly resistant to microbial attack (Kaplan et al, 19791, fungal biodegradation of lignopolystyrene graft copolymers has been reported (Milstein et al, 1992). White-rot basidiomycetes, including P. chrysosporium, were able to degrade LPS (lignin-polystyrene) graft copolymers.…”
Section: Modified Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…found no signs of degradation of a polystyrene sheet buried in soil for 32 years. Incubation of a polystyrene‐starch copolymer with Bacillus coagulans and of polystyrene–lignin copolymers with fungi showed that the polymers supplemented with starch or lignin was indeed degraded. In a similar approach, it was reported that insertion of various mono‐ or disaccharides into the carbon backbone of polystyrene increased its biodegradability .…”
Section: Resultsmentioning
confidence: 99%